Analisis Penggunaan Anggaran Biaya Administrasi Umum Dan Efisiensi Terhadap Peningkatan Kinerja Supervisor (Studi Kasus pada PT. Lautan Teduh Interniaga Bandar Lampung) - Chairul Anwar; Yunita Sari; Tina Miniawati Barusman (Universitas Bandar Lampung (UBL), 2012)
The purpose and usefulness of this research is to determine how the role of a budget on performance the supervisor in the use of general administrative expenses on PT. Lautan Shady Interniaga and to find out what factors that affect the performance of the supervisor in the use of general administrative expenses on PT. Lautan Interniaga Shade, as well as thought-provoking contributions in conducting research related to the management and general administration cost budget planning, adding insight and knowledge that could be useful for those who need especially fellow students. PT. Lautan Shady Interniaga is a company that uses the General administrative expenses and is managed by a supervisor of finance and public administration section. Supervisor of finance and public administration section on PT. Lautan Shady Interniaga is assigned to merakapitulasi the sales and operational costs related to financing activities as a whole. General administrative expenses was issued within the framework of the supervision and administration of the services of any company functions. The efficiency of performance or whether the supervisor of finance and General Administration section can be seen from the results of its realization in general administrative expenses budget.